Influence of the concept of social epistemology on the metatheory of librarianship - Drmanac, Mirko (Sociološki pregled, 2024)
This paper will consider the formation of the theoretical-methodological concept of social epistemology as an attempt to determine the scientific status of librarianship in the conditions of the scientific-technological revolution and under the influence of the sociological ideas of the Chicago School. The emergence of the first computers, new information media and electronic networks was accompanied by the fear that the book would be overcome and that librarianship would be a superfluous and anachronous activity. Jesse Hauk Shera, the founder and leading supporter of social epistemology tried to offer it as an alternative to the classical theory of librarianship. The analysis of Shera’s and other relevant works offers insights about this concept, although conceived within theoretical librarianship, not being complementary to traditional professional specifics. Although today social epistemology is accepted as a philosophical theory of cognition, in the context of librarianship and information science, it has not solved the problem of the scientific and professional identity in the conditions of modified technological reality.
Keywords: librarianship; bibliographical method; librarianship and information sciences; social epistemology; sociology of knowledge; philosophy of science; Jesse H. Shera